Doing gender diversity : readings in theory and real-world experience - Plante, Rebecca F.; Maurer, Lis M. (Routledge, 2018)
"This cutting-edge reader demonstrates the multiple ways in which the universe of gender is socially, culturally, and historically constructed. The selections focus on gender itself - how gender operates socioculturally, exists, functions, and is presented in micro and macro interactions. In order to avoid balkanization, the authors examine the various ways in which culture intersects with individuals to produce the range of presentations of self that we call 'gender', from people born male who become adult men to lesbian women to transmen, and everyone else on the diverse gender spectrum"--Publisher's description.